"5" cardinal points of an "education for citizenship" (Journal of Parents and Teachers, 2014)
Technologies, the political world and society will always evolve, which is why there is an urgency to incorporate citizenship as a subject in the education system. Education provides a sense of belonging, it is a place for socialising that many consider more important than family or religion; schools are micro-environments where certain events have an impact on those who attend them, which is why, although schools should not be the only ones to teach what citizenship truly is, it is imperative that they do so. Citizenship educates for democracy, pluralism and collective engagement. The school that practises citizenship education must (among other things) use active pedagogical methods, encourage the practice of democracy and a sense of responsibility, and engage its pupils in community service.
Keywords: citizenship; society; democracy; responsibility; school; education; community